Hubungan Peer Conformity dengan Perilaku Kenakalan pada Santri Pondok Pesantren “X” Ciamis - Mutiara Salma Syifa; Lilim Halimah (UNISBA Press, 2023)
Abstract. Delinquent behavior is a component of maladaptive behavior that can occur in adolescents. Delinquent behavior can occur in various settings, including educational settings, such as the case of delinquent behavior among teenage students at